Correction: Seed germination ecology of Conyza stricta Willd. and implications for management. - Safdar Ali; Fakhar Din Khan; Rehmat Ullah; Rahmat Ullah Shah; Saud Alamri; Maeesh AlHarthi; Manzer H Siddiqui (PLoS ONE, 2021)
[This corrects the article DOI: 10.1371/journal.pone.0244059.].